Offenbarung und Episteme: Zur europäischen Wirkung Jakob Böhmes im 17. und 18. Jahrhundert - Kühlmann, Wilhelm (Frühe Neuzeit, 2012)
For the first time, these proceedings from an interdisciplinary and international symposium use a broad foundation of sources to examine the first period (1620-1790) in the history of the major European impact of Jakob Böhme, a history that extended well into the 20th century. The contributors reveal the conflicted and contrasting patterns and modalities of reception along with the different positions taken in response to Böhme in the works of important cultural figures. These studies show the existence of a conflict zone in intellectual history and also in the history of language and literature that extended beyond the German-speaking world. Wilhelm Kühlmann, Universität Heidelberg; Friedrich Vollhardt, Universität München.
Beiträge gehen auf eine Tagung zurück, die vom 21. bis 24. April 2010 in München stattfand. - Beitr. teilw. dt., teilw. engl
Keywords: Electronic books; Konferenzschrift -- 2010 -- München; Konferenzschrift; Geschichte 1620-1790; Rezeption; Böhme, Jakob